THE INFLUENCE OF SOCIAL MEDIA AND RECRUITMENT ON THE EFFECTIVENESS OF THE EMPLOYEE SELECTION PROCESS AT PT. GUNBUSTER NICKEL INDUSTRY IN NORTH MOROWALI REGENCY - Sarah Dwiyana Kolupe; Syahir Natsir; Andi Indriani Ibrahim; Ega Nugraha (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of social media and recruitment on the effectiveness of the employee selection process at PT. Gunbuster Nickel Industry, North Morowali Regency. The study uses a quantitative approach with an associative research type. The research sample consisted of 99 employees selected using the Proportional Stratified Random Sampling technique . Data were collected through questionnaires and analyzed using multiple linear regression with the help of IBM SPSS Statistics version 25. The results of the study indicate that social media has a positive and significant effect on the effectiveness of the employee selection process. Recruitment also has a positive and significant effect on the effectiveness of the employee selection process. Simultaneously, social media and recruitment have a positive and significant effect on the effectiveness of the employee selection process . These findings indicate that the use of social media supported by an effective recruitment process has an important role in increasing effectiveness.